1996
DOI: 10.1021/jf950472a
|View full text |Cite
|
Sign up to set email alerts
|

Oxalic Acid and Calcium Determination in Wild Edible Plants

Abstract: The contents of oxalic acid and calcium in several wild edible plants were analyzed. Oxalic acid was determined by an espectrophotometric method based on the decrease of absorbance at 335 nm due to the dissociation of the zirconium(IV)−chloranilate complex, consecutive to the addition of oxalic acid. Calcium was determined by atomic absorption spectroscopy. The results show the absence of this acid in two of the studied plants:  hoary cress (Cardaria draba (L.) Desv.) and vervain (Verbena officinalis L.). Als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 2 publications
2
51
1
1
Order By: Relevance
“…Scolymus hispanicus and Silybum marianum. This may indicate that vitamin C in plants is often located at higher levels in photosynthetic tissues, as previously reported by Loewus As also found by Guil, Torija, Giménez, Rodríguez-García, & Giménez (1996), oxalic acid was the major organic acid in the basal leaves of all the analyzed non-cultivated species (Table 2), except in Taraxacum obovatum and Cichorium intybus that revealed malic acid as the main organic acid with values around 106.20 and 92.51 mg/100 g, respectively. Other authors previously reported high oxalic acid accumulation in the leafy tissues of some species from the families Asteraceae, Euphorbiaceae, Chenopodiaceae, Portulacaceae or Liliaceae, which has been attributed to the way of incorporation of HCO 3 -and CO 2 in photosynthesis mechanisms, for organic acid biosynthesis pathways.…”
Section: Vitamin C and Organic Acids Compositionsupporting
confidence: 84%
See 1 more Smart Citation
“…Scolymus hispanicus and Silybum marianum. This may indicate that vitamin C in plants is often located at higher levels in photosynthetic tissues, as previously reported by Loewus As also found by Guil, Torija, Giménez, Rodríguez-García, & Giménez (1996), oxalic acid was the major organic acid in the basal leaves of all the analyzed non-cultivated species (Table 2), except in Taraxacum obovatum and Cichorium intybus that revealed malic acid as the main organic acid with values around 106.20 and 92.51 mg/100 g, respectively. Other authors previously reported high oxalic acid accumulation in the leafy tissues of some species from the families Asteraceae, Euphorbiaceae, Chenopodiaceae, Portulacaceae or Liliaceae, which has been attributed to the way of incorporation of HCO 3 -and CO 2 in photosynthesis mechanisms, for organic acid biosynthesis pathways.…”
Section: Vitamin C and Organic Acids Compositionsupporting
confidence: 84%
“…For those reasons although oxalic acid has a quite low toxicity (with 5 g as the minimal lethal dose for an adult), the ingestion of high levels of this organic acid is not desirable. Some authors (Guil et al, 1996) recommended an oxalic acid/Ca ratio not higher than 2.5 in the foods to avoid this toxic effect.…”
Section: The Fleshy Midribs Of Silybum Marianum and To A Lesser Extementioning
confidence: 99%
“…For this reason, the ingestion of foods with high levels of this antinutritional compound is not desirable. Some authors (Guil et al, 1996) recommend an oxalic acid/Ca ratio not higher than 2.5 to avoid this negative effect. Among the selected plants, this limit is greatly exceeded by M. fontana (∼11.8) but also by other species, namely B. maritima, C. ambrosioides, S. marianum, R. pulcher, A. nodiflorum, A. acutifolius, S. oleraceus, P. oleracea, N. officinale and R. papillaris ( Fig.…”
Section: Oxalic Acidmentioning
confidence: 99%
“…Wild plants of the genus Oxalis, Rumex, Amaranthus and Chenopodium have been referred as having significant levels of oxalic acid (Guil et al, 1996;Vizgirdas and Rey-Vizgirdas, 2006). Amounts between 137 and 256 mg/100 g were described for R. pulcher, R. papillaris (Morales et al, 2014;Sánchez-Mata et al, 2012) and R. acetosella ; but a small amount of 0.7 mg/100 g was reported in tender leaves of R. induratus (Pinela et al, 2016c).…”
Section: Oxalic Acidmentioning
confidence: 99%
“…For example, oxalic acid has been reported in C. album L. (lambsquarters) in some studies, and this antinutrient could reduce the bioavailability of calcium (Guil et al, 1996(Guil et al, , 1997). While it is not possible to discuss all aspects of potential antinutritional factors in a scientific report on nutrient composition of native plant foods, obviously any contraindications with respect to consumption of wild plants and any mitigation of those factors that might occur in different preparations (e.g.…”
Section: Discussionmentioning
confidence: 99%